2020
DOI: 10.3390/s20082393
|View full text |Cite
|
Sign up to set email alerts
|

Facial Expressions Recognition for Human–Robot Interaction Using Deep Convolutional Neural Networks with Rectified Adam Optimizer

Abstract: The interaction between humans and an NAO robot using deep convolutional neural networks (CNN) is presented in this paper based on an innovative end-to-end pipeline method that applies two optimized CNNs, one for face recognition (FR) and another one for the facial expression recognition (FER) in order to obtain real-time inference speed for the entire process. Two different models for FR are considered, one known to be very accurate, but has low inference speed (faster region-based convolutional neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 42 publications
0
36
0
2
Order By: Relevance
“…Although different, highly accurate CNN-based FER models have been developed in the literature over the last decade [ 22 ], their integration into a robotic platform was not yet proven effective. Of note, the CNN architecture reported by Melinte et al, which was successfully integrated into the NAO robotic platform and demonstrated to perform better than the proposed CNN-based FER model in the same task, was not actually evaluated in human–robot interaction conditions [ 43 ]. On the other hand, testing the CNN architecture developed and integrated into the robotic platform with human participants would allow one to assess its performance in real-world scenarios, paving the way for its implementation in robotics applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although different, highly accurate CNN-based FER models have been developed in the literature over the last decade [ 22 ], their integration into a robotic platform was not yet proven effective. Of note, the CNN architecture reported by Melinte et al, which was successfully integrated into the NAO robotic platform and demonstrated to perform better than the proposed CNN-based FER model in the same task, was not actually evaluated in human–robot interaction conditions [ 43 ]. On the other hand, testing the CNN architecture developed and integrated into the robotic platform with human participants would allow one to assess its performance in real-world scenarios, paving the way for its implementation in robotics applications.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, a higher recognition rate for the angry and scared facial expressions should be achieved. Secondly the CNN’s architecture could be enhanced by employing, for instance, ResNet or Visual Geometry Group (VGG) model-based architectures, which have recently been shown to have great potential in this field [ 43 ]. Future research will focus on optimizing the CNN model in order to increase its performance, as well as testing it for complex human–robot interaction tasks such as those in the medical or neuropsychological fields.…”
Section: Discussionmentioning
confidence: 99%
“…For a social robot to provide effective services, identifying the user’s intent is paramount. A recent human-robot interaction study applied deep neural networks to recognize a user’s facial expressions in real time [ 36 ]. Further recognition of the user’s false (e.g., deception) or pretended (e.g., to be polite) expressions might introduce more social, rich, and effective interactions.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The effectiveness of several deep learning models of facial expression recognition, such as SSD and fast R-CNN for human–robot interaction is very interesting, deeply analysed and verified [ 10 ]. Based on an innovative end-to-end pipeline method that applies two optimized CNNs, the face recognition (FR) and the facial expression recognition (FER), using deep convolutional neural networks (CNN) for the growth real-time inference speed of the entire process is achieved, leading to a high level of advanced intelligent control in the interaction between humans and a NAO robot.…”
Section: Review Of the Contributions In This Special Issuementioning
confidence: 99%